The Development of Genially and Kahoot-Assisted Contextual Teaching and Learning Approach to Improve Students’ Mathematical Reasoning Ability and Habits of Mind on Junior High School - Riki Candra; Heris Hendriana; Tatang Supriatna ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
Mathematics is a subject that requires not only computational skills but also strong reasoning abilities. However, many junior high school students struggle to develop mathematical reasoning due to conventional teaching methods that often lack context and interactivity. This study aims to examine the effectiveness of a Contextual Teaching and Learning (CTL) model integrated with Genially and Kahoot in improving students’ mathematical reasoning ability. A quasi-experimental design with a pretest–posttest control group was employed. The participants were eighth-grade students divided into an experimental class, which received CTL-based learning supported by Genially and Kahoot, and a control class, which received conventional instruction. Data were collected using a validated and reliable mathematical reasoning test administered before and after the intervention. Descriptive statistics were used to summarize the data, while inferential analysis, including the Mann–Whitney test and effect size calculation, was conducted to determine the significance and magnitude of the intervention’s effect. The results indicate that students in the experimental class achieved significantly higher posttest scores compared to the control class. The effect size analysis revealed a large effect, demonstrating that the CTL model assisted by Genially and Kahoot had a strong impact on enhancing students’ mathematical reasoning ability. These findings suggest that integrating contextual learning with interactive digital media can effectively support students’ understanding and reasoning in mathematics. Therefore, the CTL model combined with Genially and Kahoot can be considered a practical and innovative alternative for mathematics instruction at the junior secondary level.